Nivel de satisfacción de los usuarios del Subcentro de Salud La Unión - Urrutia Ochoa, Ariana Gonzalina (2018)
The "La Unión" Health Subcenter located in Juan Chanalata and La 40 streets of the La Unión parish, belonging to the Babahoyo canton, province of Los Ríos, is a public establishment in charge of providing primary medical care to all people belonging to the parish and its surrounding precincts. The Subcenter has services of dentistry, general medicine, obstetrics, psychology and pharmacy